PENGARUH MANAJEMEN LABA, CURRENT RATIO, DAN FINANCIAL LEVERAGE TERHADAP INITIAL RETURN - Rofika, Rofika; Nurixmal; Novita Indrawati (Jurnal Kajian Akuntansi dan Auditing, 2024)
This research intends to examine how influencing factors including earnings management, current ratio, and financial leverage influence IPO returns. Financial leverage is monitored by the DER ratio, while earnings management is evaluated using the distributive accrual modified Jones method. Companies listing on the Indonesia Stock Exchange as part of an initial public offering (IPO) between 2016 and 2019 make up the population. 153 businesses were selected at random from the pool of potential respondents using a purposive sampling method. Multiple linear regression is the method of analysis used here. According to the findings of this research, the current ratio and financial leverage affect initial return whereas earnings management does not